Pericardium Point 6 Acupressure For Nausea, Vomiting In 1st Trimester Pregnant Women: Case Study - Permata, Annisa Devi (Nursing Case Insight Journal, 2024)
Nausea and vomiting usually occur in the morning, but some occur at any time and at night occur as a result of changes in the endocrine system that occur during pregnancy, especially increased hormones hCG in pregnancy. Data in Indonesia shows that 50% to 80% of pregnant women experience nausea and vomiting and approximately 5%. Pregnant women require treatment for fluid replacement and electrolyte correction. This case study aims to provide nursing services to pregnant women with nausea and vomiting using acupressure.  The author uses a descriptive analytical method in the form of a case study approach in patient care which includes assessment, death diagnosis, death planning, death implementation, death evaluation, and use of EBP (Evidence-Based Practice) interventions. Midwives are expected to be able to apply P6 acupressure intervention to pregnant women as a complementary therapy to reduce nausea and vomiting experienced by pregnant women which can be given to pregnant women reduce complaints of nausea and vomiting in the first trimester of pregnancy.